Corporate leadership and the myth of the incompetent Malay Chief Executive Officers: evidence from the Malaysian General Insurance Industry - Khairudin Damhoeri,; Fuat Mashori,; Jaafar Mohamad,; Kamarudin Sharif, (Penerbit Universiti Kebangsaan Malaysia, 1994)
The dearth of Malaysian based literature on leadership In general, and corporate leadership in particular suggests that Malaysian scholars and investors are yet to be sensitized to the importance of leadership as a determinant of organizational outcomes. Arguably, this inattention helps perpetuate many unhealthy myths about corporate leadership. Notable among these myths, is that of the incompetent Malay managers. In examining the myth, this study takes a quantitative perspective of an otherwise "qualitative'" subject. Using emprical eVidence from the general insurance industry, this study demonstrates that Malay chief executive officers (CEOS) , despite the myth and market perceptions, do not affect corporate performance any differently than non-Malay CEOs.